Earnings shocks and tax-motivated income-shifting: Evidence from European multinationals - Dhammika Dharmapala; Nadine Riedel (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2011)
This paper presents a new approach to estimating the existence and magnitude of taxmotivated income shifting within multinational corporations. Existing studies of income shifting use changes in corporate tax rates as a source of identification. In contrast, this paper exploits exogenous earnings shocks at the parent firm and investigates how these shocks propagate across low-tax and high-tax multinational subsidiaries. This approach is implemented using a large panel of European multinational affiliates over the period 1995-2005. The central result is that parents' positive earnings shocks are associated with a significantly positive increase in pretax profits at low-tax affiliates, relative to the effect on the pretax profits of high-tax affiliates. The result is robust to controlling for various other differences between low-tax and high-tax affiliates and for country-pair-year fixed effects. Additional tests suggest that the estimated effect is attributable primarily to the strategic use of debt across affiliates. The magnitude of income shifting estimated using this approach is substantial, but somewhat smaller than that found in the previous literature.
urn:nbn:de:bsz:100-opus-5387
Keywords: 330